"There's More Than One Right Path to The Destination": Does Degree Type Make a Difference in Police Recruiting?. Issue 3 (3rd July 2018) - Huey, Laura; Peladeau, Hillary; Kalyal, Hina
Abstract : Each year colleges and universities market criminology and criminal justice programs to potential applicants by suggesting these programs offer a uniquely tailored path for those seeking entry into a policing career. Despite such claims, little empirical research exists to suggest that degree content is a factor in influencing recruitment outcomes. In this paper, we present results from an ongoing, exploratory study into pre-recruitment education to show that program content—in this case, a criminology or criminal justice diploma or degree—has generally little influence on how police agencies evaluate a potential applicant. Drawing on interviews with thirty-two ( n = 32) police recruiters and senior officers from police services across the province of Ontario in Canada, we show that, while many agencies prefer candidates with degrees, criminology and criminal justice degree holders are not privileged in the recruiting process over those applicants from other disciplines.